The supply side of CO₂ with country heterogeneity - Michael Hoel (Center for Economic Studies and ifo Institute (CESifo), 2011)
Several recent articles have analyzed climate policy giving explicit attention to the non-renewable character of carbon resources. In most of this literature the economy is treated as a single unit, which in the context of climate policy seems reasonable to interpret as the whole world. However, carbon taxes and other climate policies differ substantially across countries. With such heterogeneity, the effects on emission paths of changes in taxes, costs and subsidies may be very different from what one finds for a hypothetical world of identical countries.
Keywords: Q31; Q41; Q42; Q54; Q58; 330; climate change; exhaustible resources; renewable energy; green paradox